2020
DOI: 10.1177/0890334420930208
|View full text |Cite
|
Sign up to set email alerts
|

Engaging African American Parents to Develop a Mobile Health Technology for Breastfeeding: KULEA-NET

Abstract: Background African Americans breastfeed less than other groups, which has implications for health throughout the life course. Little is known about mobile health technologies to support breastfeeding. Research aims This study proceeded in two phases. The aim of Phase 1 was to identify ideal technological components and content of a mobile health intervention. The aim of Phase 2 was to determine the usability of a prototype, KULEA-NET, based on the Phase 1 findings. Methods For this mixed-methods study, we used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 30 publications
(37 reference statements)
0
16
0
Order By: Relevance
“…Like our focus group participants, women in this study asked for peer discussions as a feature of mobile health technology. 13 In a study looking at technology and COVID-19 communications, investigators found that Black respondents were more likely than NHW respondents to report posting COVID-19-related content on social media. 14 Understanding technological challenges and engagement in populations of interest is critical to ensure that technology is utilized to improve healthcare for all.…”
Section: Discussionmentioning
confidence: 99%
“…Like our focus group participants, women in this study asked for peer discussions as a feature of mobile health technology. 13 In a study looking at technology and COVID-19 communications, investigators found that Black respondents were more likely than NHW respondents to report posting COVID-19-related content on social media. 14 Understanding technological challenges and engagement in populations of interest is critical to ensure that technology is utilized to improve healthcare for all.…”
Section: Discussionmentioning
confidence: 99%
“…A total of twenty articles were included in the review [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. A significant portion of the included articles were original research (n=18) [13,[15][16][17][18][19][20][21][22][23][24][25][26][28][29][30][31][32]. One perspective piece and one review were also included [14,27].…”
Section: Overviewmentioning
confidence: 99%
“…The articles that focused on general technologies explored the inclusion and specific views of Consumer Health Informatics for Racial and Ethnic Minoritized Communities: Minor Progress, Major Opportunities racial and ethnic minoritized populations [18,19,27]. Though most literature had a particular emphasis on African Americans [13,14,16,21,[23][24][25]28], there is still a dearth of literature focused on designing consumer health IT for this community. There were significantly fewer articles focused on indigenous communities [15,17,20,30,31] and Hispanic populations [22].…”
Section: Populations and Topicsmentioning
confidence: 99%
See 2 more Smart Citations